Ontem, luta pela terra; hoje monumento histórico : a revolta dos posseiros no sudoeste do Paraná em suas variadas versões - Amancio, Silva Maria (2009)
In this dissertation, we attempt to analyze, mainly, the different versions concerning to the Settlers' Revolt, held in southwestern Paraná in the year of 1957. This uprising came due to the dispute on the ownership of land in the region, between settlers and colonizer companies. The companies had the support of the state's governor, Moisés Lupion, coreligionist politicians of the Social Democratic Party (PSD) and newspapers such as "Gazeta do Povo" and "O Dia". On the other hand, the settlers had the support of politicians of the National Democratic Union (UDN), the Brazilian Labor Party (PTB) and newspapers such as "O Estado do Paraná" and "Tribuna do Paraná", groups that were opposed to the state government. Each one of these antagonistic groups used to express different versions about the Settlers' Revolt, according to their interests in the political arena. Thus, each version presents narratives with different emphases, focusing or hiding certain aspects of the conflict. The conflict's outcome was favorable to the settlers, who obtained the legal possession of the land in the southwest region. This victory enabled the construction of an official memory that turned the revolt into a historic symbol for the region. However, some aspects of this memory are countered by the reminiscences of people who lived in 1957 and, by expressing their personal identity, present particular versions of the events of 1957. Thus, analyzing these different versions, in other words, the narratives of the time, the official memory and individual memories built over the conflict, we attempt to identify poorly explained issues and ignored information about the events that marked the southwest region of Paraná.